Countercurrent chromatographic isolation and purification of 11′-α-tocomonoenol from the vitamin E extract of palm oil - Müller, Marco; Hammann, Simon; Vetter, Walter (Food Chemistry, 2018)
A new vitamin E homologue, α-tocomonoenol was detected in palm oil, but was not isolated in large amounts and with high purity so far. Here we present an easy and fast method to isolate α-tocomonoenol from vitamin E rich nutrient capsules with countercurrent chromatography (CCC). With the solvent system n-hexane – benzotrifluoride – acetonitrile (10:3.5:6.5, v/v/v) about 30 mg α-tocomonoenol with a purity of 75% could be enriched in one step from 1 g crude sample. Column chromatography with 20% deactivated silica gel and n-hexane – ethyl acetate (95:5, v/v) was performed to gain 5.6 mg α-tocomonoenol with a purity of 99.5% according to GC/MS. Structural verification by 1H NMR spectroscopy verified that the double bond was located in 11′-position (11′-α-tocomonoenol). The trace impurity detected in the isolate was identified to be 12′-α-tocomonoenol, a compound previously detected in marine samples.
Keywords: NMR spectroscopy; Palm Oil; Countercurrent chromatography; GC/MS; Tocomonoenol; Vitamin E